Health and well-being of rotation workers in the mining, offshore oil and gas, and construction industry: a systematic review - Suzanne Robinson; Daniel Powell; Dominika Kwasnicka; Bernard Yeboah-Asiamah Asare (BMJ Global Health, 2021)
Introduction Rotation work, characterised by travelling long distances to work in isolated areas where workers typically rotate consecutive days working and living on-site with periods at home, is increasingly used in the resources and construction sectors globally. Such employment practices may have an impact on workers’ health and well-being. This systematic review explores the impact rotation work has on mental and physical outcomes in rotation workers in the resources and construction sectors.Method The PubMed, Medline, EMBASE, CINAHL, PsycINFO, and Scopus databases were systematically searched on 1 May 2020 to identify quantitative, qualitative and mixed-method studies addressing the health of rotation workers published in peer-reviewed journals. Findings from the studies were summarised narratively.Results Of 6268 studies retrieved, 90 studies were included in the review. Studies suggested higher prevalence of psychological distress in onshore rotation workers and higher overweight/obesity rates among rotation workers as compared with the general population. We found more sleep problems and higher levels of smoking during work periods compared with off-site days; and higher alcohol intake during off-site days compared with on-site days. Workers generally perceived their physical health status as good. High-perceived job demands (such as workload, repetitive work) were associated with mental distress and exhaustion, sleep problems and perceived poor physical health status, while high-perceived job resources (such as job clarity/control, support) were associated with low mental distress and exhaustion, less smoking and alcohol intake, and better sleep.Conclusion Rotation work is associated with several poorer health behaviours and outcomes, such as sleep problems, smoking, alcohol consumption and overweight/obesity. Interventions needed to improve rotation workers’ health should include maximising available job resources and reducing job demands. Further longitudinal studies are needed to explore the long-term health effects of rotation work and the short-term contextual effects of the different aspects of rotation work.